2015
DOI: 10.1007/s11920-015-0570-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurology Issues in Schizophrenia

Abstract: Schizophrenia ranks among the leading causes of disability worldwide. The presence of neurological signs co-occurring with the psychiatric symptoms is indicative of an organic brain pathology. In the present article, we review the current literature on neurology issues in schizophrenia. Firstly, common neurological signs found in patients with schizophrenia (neurological soft signs and smell abnormalities) and their association with imaging findings are reviewed. Secondly, the significant association of schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 64 publications
2
17
0
1
Order By: Relevance
“…The lack of receptors causes neuropsychiatric symptoms, attributable to ovarian teratomas and autoimmune processes in approximately half of the cases [24, 6, 8]. Recognizing the symptom complex is crucial to diagnosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of receptors causes neuropsychiatric symptoms, attributable to ovarian teratomas and autoimmune processes in approximately half of the cases [24, 6, 8]. Recognizing the symptom complex is crucial to diagnosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…The communication between the disciplines of neurology and psychiatry is of high importance in these cases, because not only antibody testing but also neurological testing might improve the diagnosis of these patients. Mild neurological symptoms are frequent in patients with psychotic symptoms [207] but could be missed because they are (a) difficult to examine in the presence of acute psychiatric symptoms; (b) less attention is paid on these examinations and (c) neurological symptoms are attributed to side effect of psychopharmacological therapy. Psychiatrists thus need to be aware of this new diagnosis in a subset of psychotic patients and education has to be provided to also perform neurological examinations or form a multidisciplinary team with neurologists (also for CSF sampling).…”
Section: Conclusion/future Directionsmentioning
confidence: 99%
“…Similarly, in 2012, a Finnish study showed a 5.5‐fold increased risk of a broadly defined psychotic illness in patients with epilepsy patients, and an 8.5‐fold risk of schizophrenia . The reverse is also true, with schizophrenia having an increased association with epilepsy as compared to other organic brain disease such as multiple sclerosis . A 2014 English case‐control study showed a 7.3% prevalence of epilepsy in patients with schizophrenia compared to 1.9% in the general population …”
Section: Introductionmentioning
confidence: 98%
“…3 The reverse is also true, with schizophrenia having an increased association with epilepsy as compared to other organic brain disease such as multiple sclerosis. 4 A 2014 English case-control study showed a 7.3% prevalence of epilepsy in patients with schizophrenia compared to 1.9% in the general population. 5 This association between epilepsy and psychotic illness such as schizophrenia is complicated by the existence of psychotic interictal and postictal states in epilepsy independent of schizophrenia, and the existence of other entities such as autoimmune encephalitides, which can present with both seizures and psychosis independent of epilepsy or schizophrenia.…”
Section: Introductionmentioning
confidence: 99%